Repetitive Behavior and Restricted Interests in Young Children with Autism: Comparisons with Controls and Stability Over 2 Years. Issue 6 (18th July 2013) - Joseph, Lisa; Thurm, Audrey; Farmer, Cristan; Shumway, Stacy
<x xml:space="preserve">Abstract</x> Restricted, repetitive and stereotyped patterns of behavior, interests and activities [RRBs] are among the core symptoms of autism spectrum disorders (ASD). Previous studies have indicated that RRBs differentiate ASD from other developmental disorders and from typical development. This study examined the presentation of RRBs as reported on the Repetitive Behavior Scale‐Revised, a caregiver report, in children with ASD [separated into autism and Pervasive Developmental Disorder‐Not Otherwise Specified groups] compared with children with nonspectrum developmental delays or typical development. We examined the role of age, cognitive functioning, sex and social communication impairment as they relate to RRBs. The stability of RRBs in children with autism was also examined over the course of 2 years. Results of the study confirmed that the amount and type of RRBs differs by diagnosis. Age, cognitive functioning, sex and social‐communication impairment were not significant correlates. Among children with autism, RRBs remained stable over time. Autism Res 2013, 6: 584–595. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.